2016
DOI: 10.1186/s12885-016-2169-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and prognosis of uncommon metastases from non-small cell lung cancer

Abstract: BackgroundAccording to the literature and our experience, the most common sites of non-small cell lung cancer (NSCLC) metastases include the brain, bone, liver, adrenal glands, contralateral lung and distant lymph nodes. Metastases to other organs are relatively rare. There have been numerous case reports and a few small case series of uncommon metastases derived from NSCLC.MethodsWe defined all organs except the common metastatic sites mentioned above as uncommon sites of metastasis. Patients with uncommon me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 20 publications
4
97
0
5
Order By: Relevance
“…In accordance with our findings, several reports demonstrated that a surgical approach to metastatic NSCLC may improve prognosis (25)(26)(27). There is a possibility that surgery was performed only on patients who were expected to have better prognosis.…”
Section: Univariate Analysis Multivariate Analysis ------------------supporting
confidence: 78%
“…In accordance with our findings, several reports demonstrated that a surgical approach to metastatic NSCLC may improve prognosis (25)(26)(27). There is a possibility that surgery was performed only on patients who were expected to have better prognosis.…”
Section: Univariate Analysis Multivariate Analysis ------------------supporting
confidence: 78%
“…nění [21,22]. Jejich přítomnost je spojena s horší prognózou pa cientů [21] a stejně jako u naší nemocné jsou obvykle spojeny s pohrudničními maligními výpotky [14].…”
Section: Obr 3 Parciální Regrese Nálezu Na Ct Při Terapii Osimertinunclassified
“…Jejich přítomnost je spojena s horší prognózou pa cientů [21] a stejně jako u naší nemocné jsou obvykle spojeny s pohrudničními maligními výpotky [14]. Kazuisticky byla doložena regrese tohoto typu metastáz po erlotinibu, který navíc dle jiné práce dokládal slibnou účinnost po léčbě afatinibem se získanou mutací C797S a delecí na exonu 19 [23,24].…”
Section: Obr 3 Parciální Regrese Nálezu Na Ct Při Terapii Osimertinunclassified
See 1 more Smart Citation
“…According to the seminal study by Quint et al [6], the main metastatic sites for LC, apart from lymph nodes, are the brain, bone, liver, adrenal glands, body wall and lung (47, 36, 22, 15, 13 and 11%, respectively). All other locations are defined as “uncommon metastases,” which have been reported as independent predictors of poorer overall survival compared to common ones [7]. Such worse outcome may be explained by 2 hypotheses: (i) tumor cells spreading and surviving in a “hostile” anlage, such as an uncommon organ, may develop a more aggressive phenotype, and (ii) treatment of metastatic cancer in uncommon sites is challenging, especially when there is only one distant localization of disease [7].…”
Section: Introductionmentioning
confidence: 99%